Improving Marketing Performance and Product Innovation Capability through Digital Knowledge Sharing: A Case Study in SME`s Food Processing - Putri Wira Paramita Dewi; Ken Sudarti (The Winners, 2022)
The research aimed to examine a mediating role of product innovation capability with customer orientation and digital knowledge sharing to increase marketing performance. The research employed a total of 185 food processing SMEs in Blora, Central Java, Indonesia who often did digital knowledge sharing. They became the respondents of the research selected by using purposive sampling. The research model was tested using multiple linear regression analysis with SPSS software. The results show that product innovation capability is proven to mediate customer orientation and digital knowledge sharing on marketing performance. Furthermore, the research expects that good customer orientation, digital knowledge sharing, and product innovation capability become the beginning of success in achieving and improving the marketing performance of food processing SMEs in Blora during the pandemic so that SMEs can continue to operate and develop. It is necessary for future research to involve some other SMEs from within and outside Blora in order to expand the population and samples.